Wpływ polityki regionalnej na ewolucję budżetu Unii Europejskiej - Smolny, Katarzyna (The Influence of Local Policy on the Evolution of European Union's Budget, 2005)
Structural funds and the Cohesion Fund constitute the basic financial instruments for the implementation of cohesion policy in EU countries. Thanks to them, various regions and countries obtain substantial financial means which enable them to finance their own strategies of economic development and adjustment processes. The main criteria of granting these means is their aim indicated by the European Union. Joining EU by Poland does not mean automatic distribution of money, but it gives us equal rights to apply for them on the basis of strictly defined rules. It is worth mentioning that within the Policy of Economic and Social Cohesion there is no restriction or transitional period for Poland. My dissertation presents some assumptions of the Integrated Operational Programme of Regional Development in the years 2004-2006 prepared by the Ministry of Labour and Social Policy in December 2003, as well as other organisational and legal instrument enabling to take advantage of structural funds in order to develop Polish regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 43-49